Study on the hybrid effect of chopped fiber and basalt fiber textile on the flexural behavior of two-way concrete slabs - Hu Chaobin; Liu Xinrong; Jin Shun; He Mingjian; LI Liping; Liang Ninghui; Fu Changrong (Case Studies in Construction Materials, 2025)
This study systematically investigated the performance optimization of basalt-fiber textile reinforced concrete (BF-TRC), focusing on the reinforcing effects and synergistic mechanisms of varying layers and spacings of fiber textiles, as well as different types of chopped fibers (basalt fibers, hooked-end steel fibers and polypropylene fibers). Four-edge simply supported bending tests on two-way slabs demonstrate that basalt fiber textiles significantly enhance the first-crack load, ultimate load, and ultimate load deflection; specimens with four layers of 20mm-spaced textiles exhibited increases of 103.08 % in ultimate load and 329.34 % in ultimate deflection compared to plain concrete, alongside substantial toughening. The toughening effect was inversely proportional to the effective utilization rate of the textile at rupture, where increasing textile layers or adding steel fibers reduced this rate, achieving toughening through a delayed stress release effect. Different chopped fibers exhibited distinct reinforcement behaviors: chopped basalt fibers increased the first-crack load by 40.91 % by suppressing textile slippage via interfacial effects; polypropylene fibers enhanced energy dissipation capacity during cracking by 22.98 % through optimized stress distribution; whereas end-hooked steel fibers demonstrated superior multi-stage bridging, increasing cumulative energy absorption by 129.02 %. Crucially, a hybrid system combining end-hooked steel fibers, chopped basalt fibers, and basalt fiber textiles achieved optimal synergy under a two-layer textile configuration, it delivered a 112.84 % increase in ultimate load and a 3.66-fold increase in ultimate deflection versus plain concrete, while providing significant toughening even with fewer textile layers, thereby optimizing material economy and applicability with strong engineering potential. Based on experimental data and mechanistic analysis, a theoretical model for textile slippage constraint incorporating fiber characteristics and interfacial interactions was established, providing a theoretical foundation for designing high-performance fiber-reinforced concrete.